Real-world outcomes of a loading phase with intravitreal faricimab in refractory Neovascular Age-Related Macular Degeneration (nAMD) patients - Xu Yufeng; Hong Ningxi; Su Mingzhi; Zheng Weixin; Ye Panpan (BMC Ophthalmology)
Abstract Background Intravitreal injection (IVI) of anti-vascular endothelial growth factor (anti-VEGF) agents is the standard of care for neovascular age-related macular degeneration (nAMD), but treatment resistance and incomplete fluid resolution remain challenges in refractory cases. This study investigates the real-world outcomes of faricimab in patients with previously treated refractory nAMD. Methods A prospective single center study was conducted involving patients with refractory nAMD treated with a loading dose of 3 IVI of faricimab 6 mg/0.05 ml, administered every four weeks. All patients included in this study had previously received a minimum of 3 consecutive intravitreal injections of other anti-VEGF. Main outcome measures included best-corrected visual acuity (BCVA) and OCT outcomes at follow-up time for 3 months. Results Thirty-five eyes of 35 patients were included. The BCVA (logMAR) improved from 0.84±0.49 to 0.76±0.49 at 3 months (P = 0.025). The central macular thickness (CMT) decreased significantly from 447.65±161.46 µm to 327.33±147.78 µm at 3 months (P < 0.001). The correlation analysis revealed that age and ellipsoid zone (EZ) discontinuity exhibited a weak positive correlation with the final BCVA (P < 0.05). Baseline BCVA demonstrated a strong positive correlation with the final BCVA (P < 0.05). Meanwhile, baseline CMT, intraretinal fluid (IRF), scar, and subretinal hyperreflective material (SHRM) showed a moderate positive correlation with the final BCVA (P < 0.05). Multivariate logistic regression analysis demonstrated that baseline BCVA (P = 0.032) and age (P = 0.047) were independent predictors of final BCVA. Conclusion In the short term, faricimab led to significant improvements in BCVA and CMT, as well as reductions in retinal fluid, making it an effective treatment option for previously treated refractory nAMD with minimal adverse effects. Limitations include the single-arm design, small sample size, and lack of long-term durability assessment.